Legal Protection of Personal Data as Listed in Court Decision: A Discourse Renewal - Tina Amelia; Nunung Rahmania; Aftab Haider (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
This study aims to examine and analyze the actualization of specific personal data protection, especially criminal records in the context of court decisions. In the digital era and advances in information technology, personal data protection is becoming an increasingly important and relevant issue. However, there is a need to better understand how specific personal data protection is realized and implemented in the context of court decisions. For example, the court decision related to divorce. In the case of a divorce that befell an artist, the court decision was published on the court's official website. The impact is that the public knows the cause of the divorce. This is a form of no protection of personal data, under the pretext of openness of court information. This study use a normative legal research method with a statue approach and a conceptual approach. The data used consists of primary legal materials and court decisions related to personal data protection. In addition, this study also refers to legal literature and expert views related to personal data protection and court decisions. The results of the study indicate that the actualization of personal data protection, especially criminal records listed in court decisions, is an exception due to the principle of open trials and published trial results. There needs to be a reformulation of the concept of exceptions to personal data protection related to criminal records in the context of court decisions. This reformulation is emphasized to avoid abuse in the judicial process and maintain public trust in the judicial system. The reformulation was carried out to clarify the position of criminal records listed in Court Decisions as excluded objects and the rights of Personal Data Subjects regulated in the Personal Data Protection Law are also excluded for Court Decisions. The implications of this study are expected to provide a better understanding for related parties, including courts, governments, and the general public, regarding the importance of specific personal data protection in the context of the courts.